A DUF3494 ice-binding protein with a root cap domain in a streptophyte glacier ice alga - Procházková, Lenka; Remias, Daniel; Nedbalová, Linda; Raymond, James A. (Frontiers in Plant Science, 2024)
Ice-binding proteins (IBPs) of the DUF3494 type have been found in many ice-associated unicellular photoautotrophs, including chlorophytes, haptophytes, diatoms and a cyanobacterium. Unrelated IBPs have been found in many land plants (streptophytes). Here we looked for IBPs in two streptophyte algae that grow only on glaciers, a group in which IBPs have not previously been examined. The two species, Ancylonema nordenskioeldii and Ancylonema. alaskanum, belong to the class Zygnematophyceae, whose members are the closest relatives to all land plants. We found that one of them, A. nordenskioeldii, expresses a DUF3494-type IBP that is similar to those of their chlorophyte ancestors and that has not previously been found in any streptophytes. The protein is unusual in having what appears to be a perfect array of TXT motifs that have been implicated in water or ice binding. The IBP strongly binds to ice and almost certainly has a role in mitigating the daily freeze-thaw cycles that the alga is exposed to during late summer. No IBP was found in the second species, A. alaskanum, which may rely more on glycerol production for its freeze-thaw tolerance. The IBP is also unusual in having a 280-residue domain with a β sandwich structure (which we designate as the DPH domain) that is characteristic of root cap proteins of land plants, and that may have a role in forming IBP oligomers. We also examined existing transcriptome data obtained from land plants to better understand the tissue and temperature dependence of expression of this domain.